Penyusunan Laporan Keuangan Berbasis SAK ETAP Koperasi Intako Dan Respon Pihak Eksternal: Preparation of Financial Statements Based on SAK ETAP Cooperative Intako and Responses of External Parties - Indawatika, Feri (Journal of Accounting Science, 2017)
This study aims to perform the preparation of financial statements in Cooperative INTAKO based SAK ETAP responses and identify external parties regarding the preparation of the financial statements based SAK ETAP. This type of research is qualitative. Data collection techniques with interviews, documentation, and triangulation. Test the validity of the data by using the test of credibility, transferability, and dependability. Engineering analysis using the data collection phase, data reduction, the data display, and conclusion. The results showed that the Cooperative INTAKO only prepare three financial statements, namely: Balance Sheet, Income Statement, and Notes to the Financial Statements and the report asled to the SAK ETAP, but there are a few post that are not yet in accordance with SAK ETAP. So the report prepared by the researchers is the Balance Sheet, Income Statement, Statement of Changes in Equity, Cash Flow Statement and Notes to Financial Statements. Supervisors Cooperative INTAKO response regarding the preparation of the financial statements based SAK ETAP is less familiar with the statement of changes inequityand cash flows. Response Diskoperindag and EMR Sidoarjo financial statements based on SAK ETAP is the format and types of financial statements that are prepared can be adjusted to the needs of the cooperative while it is in accordance with thelawon cooperatives and applicable accounting standards. Cooperative Response Putra Buana Waru financial statements based on SAK ETAP is too complicated if the cooperative must prepare complete financial statements for cooperatives prepare financial reports as needed and cooperative laws still give leeway regarding the preparation of the financial statements of the cooperative.